Research of methodological tools for improving the graphic abilities of future designers and architects (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
At the current stage, higher education is moving to a new qualitative level,reflecting innovations in the professions of "Designer" or "Architect". Hence, the need for traininghighly qualified specialists in these fields is growing. Given modern concepts and innovativetechnologies that are evident in all spheres of human life, the requirements for the level ofprofessional training of graduates of higher educational institutions, their self-education, the abilityto think independently, optimize their activities, and make unconventional, non-trivial decisionshave increased. The development of relevant high-quality graphic competencies and sustainablepractical skills in the process of training future creative specialists is a pressing issue. For juniorstudents, especially in design and architecture, freehand drawing remains a fundamental skill thatrequires systematic development through special techniques and exercises. The main goal is to"train the hand", develop an eye, a sense of proportion and confidence in line. The development ofhand graphics is inextricably linked with classical graphic disciplines, primarily the following:"Sketchy Geometry", "Geometry of Images", "Font Graphics" or "Art of Font", "Accidental Font","Typographyk", etc. The main results of the study of methodological tools for improving thegraphic capabilities of future designers and architects are reviewed by the authors using extensiveresearch in the process of teaching first-year or second-year students graphic disciplines at theDepartment of Descriptive Geometry and Engineering Graphics of Odesa State Academy of CivilEngineering and Architecture (OSACEA). The research used analytical methods to summarizeexpert assessments of graphic and individual, in particular competitive, student works, the results ofhourly observations of the performance of tasks in classroom classes provided for by thecurriculum, and conclusions from a critical comparative analysis of modern publications on themethodology of teaching graphic disciplines to students with a creative profile, etc. The researchresults were tested in the educational process, which provides for the improvement anddevelopment of this topic in the future.
Keywords: Descriptive Geometry; graphic disciplines; junior students of design and architecture majors; technical literacy